Homage to political philosophy : the good society from Plato to the present - Flynn, James R. (James Robert), 1934- (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2018)
"This book offers a model introduction to political philosophy, addressing philosophers from Plato to Rawls and Nozick, with each thinker treated as exploring perennial problems. These include ethical truth, free will, the common good, whether God exists, whether America could become a Hobbesian world sovereign, appeals to nature, free speech, the nature of rights, how one can argue with Nietzsche, whether history is predictable, whether the market can be humanized, and assumed genetic differences between races and genders. When a thinker poses a problem not resolvable at that time, (such as racial equality) modern social science and economics are used to provide answers. There are two persistent themes in this book: namely, that a futile search for ethical truth has drained the original image of the good society (Plato and Aristotle) of its rich content, and that the market has replaced justice as the ordering principle of human society leaving philosophers helpless unless they learn economics."--
Political philosophy dead or alive -- Preface to Plato -- Plato and Thrasymachus -- Slavery and race -- Aristotle and Leo Strauss -- Men and women -- Aquinas and your soul -- Does God exist? -- Hobbes and the state of nature -- The America who would be king -- Locke and Rousseau -- Appeals to nature -- Mill and utilitarianism -- Free speech and the universities -- Benedict and James -- Postmodernism -- Nietzsche and Sartre -- Oxbridge nice ethics -- Marx and history -- Do we have a future? -- Ayer and moral language -- How to conduct a moral debate -- Tawney and rights -- Humanizing the market -- Rawls and Nozick -- Huxley and Skinner -- Is free will possible? -- Scientific humanism.
Incluye referencias bibliográficas (páginas 394-405) and indexes.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Political science -- Philosophy -- History; Libros electrónicos.